(untitled) (Journal of the College of Basic Education, 2026)
Lithium Fluoride (LiF) thin films were prepared by thermal evaporation under vacuum (TEV), on glass substrate at room temperature of (303K). After that the films were treated thermally at temperature of (473,573 K) for one hour, with thickness of (400±10 nm). The optical properties of (LiF) thin films were studied within the wavelength range of (200-1100) nm. It was found that it has a high transmittance between (80 – 95 %) percentage, and low absorption and reflectivity in the (visible, near infrared) region. The value of energy gap was calculated and it was found that it is value is (5.1 eV) and the energy gab decreased to (5eV) with increasing annealing temperature. The value of some optical constants such as Absorption (α), Extinction coefficient (Kο) and Reflective index (n) were also calculated